ASSESSMENT OF PREVALENCE OF DEPRESSION IN CARDIAC PATIENTS AND ITS ASSOCIATION WITH THE USE OF BETA-BLOCKERS AND STATINS - Desai, Krutika; Diwan, Neha; Mudhiganti, Perin Devi; Joshi, Anand V; Boggula, Narender; Bakshi, Vasudha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study is to assess the prevalence of depression among patients with cardiovascular disease and its association with the use of Î²-blockers and statins. Methods: This is a prospective observational study conducted at a corporate hospital, Hyderabad, Telangana, India, for a period of 6 months. 250 cardiac patients above 16 years are included in the study. The required data are collected from the patients through direct interview using standard questionnaires and also from patients' respective case sheets. The acquired data are evaluated based on the standard questionnaires Patient Health Questionnaire-9 (PHQ-9) and Beck Depression Inventory-II (BDI-II) scales; used to diagnose the severity of depression in cardiac patients. Results: Prevalence of minor to major depressive symptoms according to BDI-II was found to be 17.2%. Prevalence of minor to major depressive symptoms according to PHQ-9 was found to be 19.2%. Among male patients, 13% showed depressive symptoms, whereas among female patients 25% showed depressive symptoms. Among the patients coadministering beta-blockers and statins, 15% were depressed according to BDI-II, and 16% were depressed according to PHQ-9 at visit. After 1 month (first follow-up), the percentage increased by 8% (for BDI-II)-12% (for PHQ-9) and remains almost the same at the second follow-up. As per BDI-II and PHQ-9 scores, the percentage of patients with minor to major depression among the patients using only beta-blockers decreased significantly from the time of visit to the second follow-up. The percentage of patients with minor to major depression among the patients using only statins increased significantly from the time of visit to second follow-up. Conclusion: Prevalence of minor to major depression according to BDI-II was found to be 17%, whereas according to PHQ-9, it was found to be 20% in patients with cardiovascular disease. Cardiovascular diseases have been more prevalent in men than in women, whereas depressive symptoms have been more prevalent in women than in men. Patients using only Î²-blockers showed a decrease in symptoms of depression. Whereas statins have shown to increase the chances of depression slightly which is often negligible, atorvastatin was associated with a higher level of depression when compared to rosuvastatin. Controversies still exist that statins decrease risk of depression. Â